Tips on pre-emptive hemostasis of large vessels during endoscopic full-thickness resection of a large gastrointestinal stromal tumor - Abdullah Abbasi, MD; Maham Hayat, MD; Saurabh Chandan, MD; Sagar Pathak, MD; Muhammad K. Hasan, MD; Kambiz K. Kadkhodayan, MD; Peter V. Draganov, MD; Dennis Yang, MD (VideoGIE)
Background and Aims: Exposed endoscopic full-thickness resection is often necessary for the management of large subepithelial lesions or those extending deep into the GI wall. Despite advances in endoscopy, our toolbox for the prevention and management of bleeding from large vessels remains limited. This video case report demonstrates the successful removal of a large gastrointestinal stromal tumor in the fundus, with a focus on our endoscopic approach to the management of large peritoneal vessels. Methods: An exposed endoscopic full-thickness resection procedure was performed using a needle-type and insulated tip electrocautery knife. Endoscopic ligation of blood vessels was performed using through-the-scope clips, whereas closure of the gastric wall defect was accomplished with over-the-scope suturing. Results: An 82-year-man with multiple comorbidities was found to have gastric fundal gastrointestinal stromal tumor on computed tomography and confirmed on endoscopic ultrasound fine-needle aspiration. After multidisciplinary discussion, he was planned for endoscopic resection. Given the size of the lesion and exophytic component, exposed endoscopic full-thickness resection was performed. Large peritoneal feeding vessels were identified. For pre-emptive hemostasis, through-the-scope clips were used for ligation before vessel transection. This approach was effective and resulted in sufficient mechanical tamponade to permit adequate visualization for targeted intervention when bleeding ensued. The remainder of the lesion was subsequently dissected without any issues. Closure of the large full-thickness defect was achieved using the over-the-scope suturing system. Conclusions: We present pre-emptive endoscopic hemostatic strategies when encountering large vessels. Innovation and development of dedicated devices are urgently needed to increase the efficiency and safety of these procedures as we continue to expand our therapeutic boundaries.